Pengaruh Reward and Punishment Terhadap Loyalitas Karyawan di PT. Columbia Perdana Cabang Manado - Kawulur, Tresia Karli; Areros, William A.; Pio, Riane J. (Sam Ratulangi University, 2018)
In carrying out an activity the company needs to conduct an evaluation (evaluation) on the implementation of human resource programs (HR) that has been developed in achieving the overall objectives of the company to ensure that the function of human resources (HR) has been running and contribute well in achievement success of the company. The purpose of this study are (1) To determine the effect of reward on employee loyalty PT. Columbia Perdana Branch Manado; (2) To know the effect of giving punishment to employee loyalty of PT. Columbia Perdana of Manado (3) To know the provision of rewards and punishment on employee loyalty PT. Columbia Perdana of Manado. Benefits of this research are: (1) for the researcher is to add insight about systematics reward and punishment to employee loyalty; (2) for the library to add collections and reference materials to other researchers in the field of field works; (3) for the company that is able to provide good input for PT. Columbia Perdana Of Manado to improve performance and loyalty and the wider community regarding appropriate rewards and punishments. This research uses quantitative descriptive method with data analysis technique using validity test, reliability test, multiple linear regression analysis, t test, f test, and test done manually and using SPSS application. Based on statistical analysis obtained results as follows: Hypothesis Test Results show that Reward and Punishment simultaneously affect the loyalty of employees of PT. Columbia Perdana Branch Manado, while punishment does not partially effect on employee loyalty of PT. Columbia Perdana Of Manado.